Learn English Fast: The secrets of fast success - Safar o'g'li, Namozov Shahrosul (Journal of Innovation in Education and Social Research, 2025)
Learning English quickly has turned out to be a necessity in the contemporary world, whereby communication, education and business in most instances require one to speak English. This paper explores the best practices of learning the English language fast with reference to vocabulary, listening, speaking and writing. The mixed-method design was used, in which 60 learners between the age of 15 and 30 people participated in the process of immersion, engagement, and task-based learning in a period of three months. The outcome of the results reveals a great enhancement in vocabulary, listening, and speaking skills, particularly on learners who had employed immersive and interactive approaches. Some of the most important elements of language acquisition that were found to be central to fast language acquisition included motivation, practice and fear of making errors. This study offers an evidence-based method among learners and teachers who want to learn English quickly.